The transcription factor TAL1 and miR-17-92 create a regulatory loop in hematopoiesis - Annekarin Meyer (Nature Portfolio, 2020)
Abstract A network of gene regulatory factors such as transcription factors and microRNAs establish and maintain gene expression patterns during hematopoiesis. In this network, transcription factors regulate each other and are involved in regulatory loops with microRNAs. The microRNA cluster miR-17-92 is located within the MIR17HG gene and encodes six mature microRNAs. It is important for hematopoietic differentiation and plays a central role in malignant disease. However, the transcription factors downstream of miR-17-92 are largely elusive and the transcriptional regulation of miR-17-92 is not fully understood. Here we show that miR-17-92 forms a regulatory loop with the transcription factor TAL1. The miR-17-92 cluster inhibits expression of TAL1 and indirectly leads to decreased stability of the TAL1 transcriptional complex. We found that TAL1 and its heterodimerization partner E47 regulate miR-17-92 transcriptionally. Furthermore, miR-17-92 negatively influences erythroid differentiation, a process that depends on gene activation by the TAL1 complex. Our data give example of how transcription factor activity is fine-tuned during normal hematopoiesis. We postulate that disturbance of the regulatory loop between TAL1 and the miR-17-92 cluster could be an important step in cancer development and progression.